7.5k views
3 votes
What is the product of 2x -5 and 3x^2 + 5x - 7? Write your answer in standard form. A. Show your work. B. Is the product of 2x -5 and 3x^2 + 5x -7 equal to the product of 5x - 2 and 3x^2 + 5x - 7? Explain your answer.

User Warao
by
5.5k points

1 Answer

7 votes

Answer:

A)What is the product of 2x -5 and 3x^2 + 5x - 7? Write your answer in standard form.

6x³ - 5x² - 39x + 35 = 0

B. Is the product of 2x -5 and 3x^2 + 5x -7 equal to the product of 5x - 2 and 3x^2 + 5x - 7?

No it is not.

Explanation:

A)What is the product of 2x -5 and 3x^2 + 5x - 7? Write your answer in standard form.

(2x - 5) (3x² + 5x - 7)

= 2x(3x² + 5x - 7) -5(3x² + 5x - 7)

= 6x³ + 10x² - 14x -15x² - 25x +35

Collecting like terms

= 6x³ +10x² - 15x² - 14x - 25x +35

= 6x³ - 5x² - 39x + 35

In standard form

6x³ - 5x² - 39x + 35 = 0

B. Is the product of 2x -5 and 3x^2 + 5x -7 equal to the product of 5x - 2 and 3x^2 + 5x - 7?

First we find the product of

5x - 2 and 3x² + 5x - 7?

(5x - 2) (3x² + 5x - 7)

5x(3x² + 5x - 7) -2(3x² + 5x - 7)

15x³ + 25x² - 35x - 6x² -10x + 14

Collect like terms

15x³+ 25x² - 6x² -35x - 10x + 14

15x³ + 19x² - 45x + 14 = 0

Hence, the product of 5x - 2 and 3x^2 + 5x - 7

= 15x³ + 19x² - 45x + 14 = 0

The product of 2x -5 and 3x^2 + 5x -7 = 6x³ - 5x² - 39x + 35 = 0

Comparing both products, we can see that

The product of 2x -5 and 3x^2 + 5x -7 ≠ the product of 5x - 2 and 3x^2 + 5x - 7

User Lapolonio
by
4.7k points